2022
DOI: 10.1017/s003329172200277x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding guilt-related interpersonal dysfunction in obsessive-compulsive personality disorder through computational modeling of two social interaction tasks

Abstract: Background Obsessive-compulsive personality disorder (OCPD) is a high-prevalence personality disorder characterized by subtle but stable interpersonal dysfunction. There have been only limited studies addressing the behavioral patterns and cognitive features of OCPD in interpersonal contexts. The purpose of this study was to investigate how behaviors differ between OCPD individuals and healthy controls (HCs) in the context of guilt-related interpersonal responses. Method A total of 113 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Like the pathological personality trait domain detachment, schizoid PD is characterized by a “pervasive pattern of detachment from social relationships and a restricted range of expression of emotions in interpersonal settings” [1], which makes impairments in emotional empathy conceptually plausible. The lack of incremental association between impairments in emotional empathy and obsessive-compulsive PD stands seemingly in contrast to an experimental study which yielded that individuals with obsessive-compulsive PD show less guilt than healthy controls [28]. However, this discrepancy can be explained by the fact that the MET measures emotional empathy based on an isomorphic matching definition; i.e., it is based on the question whether the participant experiences the same emotion as the depicted person, while the social interactive task used by Xiao et al [28] aims to induce guilt, e.g., by non-cooperative behavior.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Like the pathological personality trait domain detachment, schizoid PD is characterized by a “pervasive pattern of detachment from social relationships and a restricted range of expression of emotions in interpersonal settings” [1], which makes impairments in emotional empathy conceptually plausible. The lack of incremental association between impairments in emotional empathy and obsessive-compulsive PD stands seemingly in contrast to an experimental study which yielded that individuals with obsessive-compulsive PD show less guilt than healthy controls [28]. However, this discrepancy can be explained by the fact that the MET measures emotional empathy based on an isomorphic matching definition; i.e., it is based on the question whether the participant experiences the same emotion as the depicted person, while the social interactive task used by Xiao et al [28] aims to induce guilt, e.g., by non-cooperative behavior.…”
Section: Discussionmentioning
confidence: 80%
“…Patients with narcissistic PD showed deficits in emotional empathy, but not in cognitive empathy, when using the MET [27]. An experimental study found impairments in guilt-related responses in obsessive-compulsive PD [28], suggesting deficits in emotional empathy. An investigation on interview-assessed metacognition in avoidant PD suggests that affected patients have difficulties in taking others’ perspectives and making plausible hypotheses about others’ mental states [29], indicating impairments in cognitive empathy.…”
Section: Introductionmentioning
confidence: 99%
“…All of these approaches use a single-person task design and mainly target hallucinatory and delusional positive symptoms, reward-related decision-making, and thought and language deficits in PSZ (Siemerkus et al ., 2019 ; Deserno et al ., 2020 ; Smith et al ., 2021 ; Charlton et al ., 2022 ; Knolle et al ., 2022 ; Limongi et al ., 2022 ). A recent study examining guilt-related interpersonal dysfunction in obsessive-compulsive personality disorder using social interaction tasks applied two computational models (guilt aversion and Fehr–Schmidt inequity aversion models), and demonstrated that interpersonal dysfunction was the result of maladjustment to and poor compliance with social norms (Xiao et al ., 2022 ). The idea of translating Bayesian predictive models to study two-person interactions at both the individual and collective levels, based on a dialectical mis-attunement hypothesis in autism, has been proposed (Bolis et al ., 2017 ).…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…Recent research has increasingly utilized computational models to explore the complex psychological components driving reciprocity [8,9,17]. Those computational models typically suggest that decisionmakers aim to maximize the utility of their choices by balancing economic benefits, such as monetary rewards, against the costs of norm violations, including anticipatory negative emotions like guilt and superiority aversion.…”
Section: Introductionmentioning
confidence: 99%
“…Research on social anxiety and generalized anxiety disorder has shown diminished generosity [21], cooperation [22], and reciprocity [23][24][25], suggesting a broad inhibitory effect of anxiety on prosocial behaviors including reciprocity. Individuals with obsessive-compulsive personality disorder (OCPD), which often co-occurs with high anxiety levels, exhibit less guilt aversion in reciprocity decisions during a binary trust game, suggesting that anxiety might attenuate anticipatory feelings of guilt by restricting affective processing and reducing their sense of moral obligation [17]. Additionally, anxious individuals tend to adopt avoidance strategies [26][27][28] and engage in excessive effortful processing when regulating emotion [29][30][31].…”
Section: Introductionmentioning
confidence: 99%